A Study to Evaluate the Effectiveness of Awareness Programme on Knowledge Regarding Disaster Preparedness For Common Natural Disasters among the Adults Residing at Selected Rural Areas of Dehradun, Uttarakhand - Manisha (Institute of Medico-legal Publications Pvt Ltd, 2021)
Disasters have a huge impact on humans, environment and economy throughout the globe. Preparedness for disasters is critical for individuals, households, businesses, organizations and communities, but many remain unprepared. India has been vulnerable to a large number of natural and human-made disasters on account of its unique geo-climatic and socio-economic conditions. The study was conducted to evaluate the effectiveness of awareness programme on knowledge regarding disaster preparedness for common natural disasters among the adults residing at selected rural areas of Dehradun, Uttarakhand. A quasi experimental study using non-equivalent control group pre-test post-test design was used. Purposive sampling technique was used to select 80 adults: 40 each in control group and experimental group. Data was collected using structured knowledge questionnaire. Collected data was analyzed by descriptive and inferential statistics using SPSS-16 programme. The findings showed that the pre-test mean knowledge score among the adults of control group was 15.88 and experimental group was15.35. The post-test mean knowledge score among the adults of control group was 16.02 whereas in experimental group it was 30.05. In post-test, in control group, maximum 62.5 % adults had average knowledge, 30% had poor knowledge and 7.5% had good knowledge, whereas in experimental group, maximum 82.5% adults had good knowledge, 17.5% had average knowledge and none had poor knowledge. Hence it was concluded that the awareness programme had significant impact on improving knowledge of adults regarding disaster preparedness for common natural disasters.